LEARNING MODEL DEVELOPMENT FRAMEWORK WITH FLIPPED CLASSROOM METHOD AND SMART LEARNING DIAGNOSIS SYSTEM FOR VOCATIONAL HIGH SCHOOL - Eka Angga Laksana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Flipped classroom has reached some popularity in last decade. Theoretically, flipped classroom means particular classroom-based learning activity are shifted into outside class hour by using videos or other eLearning materials while common class time is spent on highly interactive learning activity. Vocational high schools especially in engineering still use tradition learning method by in-class learning and homework after class. In order to increase learning quality and learning engagement, the author propose a research framework to implement flipped learning. Flipped learning also can be designed to increase literation score because according to the survey that PISA score in Indonesia needs to be increased. This paper proposes a framework to design implementation flipped learning in vocational high school and evaluation using intelligent system. Hence, the other schools could take benefit and review what is the advantage, evaluation scheme and cost planning of this topic.